A woman among men: Christine de Pizan's bibliographical gesture in The City of Dames - Siciliano, Mell; Valle, Fernanda; Salomão, Amanda (Bibliothecae.it, 2021)
This paper is a theoretical and exploratory research on the concepts of bibliography and bibliographic gesture, in relation to the book The Book of the City of Ladies, by Christine de Pizan (1363-1431 AD). In this work, the Italian author based in France, disputes the widely revered and referencedpatriarchal bibliography, by selecting 150 female personalities who stood out in various fields of knowledge, by means of a logical argument as well as a memorial to female reputation. The discussion hereby presented is supported by the literature review performed by Eduardo Alentejo (2015) - to whom bibliography is understood both as a material and intellectual product, under the notion of repertoire, lists or subject descriptions, always guided by general policies and individual choices of bibliographers, thus related to selection, and clipping – and by the notion of bibliographic gesture, as defined by Giulia Crippa (2015, 2016). Other authors like André Araújo (2015), Viviane Couzinet and Patrick Fraysse (2019) are useful to better understand the concept of bibliography; and, to contextualize Christine de Pizan in her time, Rosalind Brown-Grant (1999), Patrizia Caraffi (2003, 2004), Diana Arauz Mercado (2005), Tracy Adams Rechtschaffen (2010), Ana Rieger Schmidt (2020a, 2020b) and Jacques Le Goff (2006). The Book of the City of Ladies was read in two versions: one translated to English (1999) and other to Portuguese (2012), both developed from the original text in Old French. The results show that, given the different existing notions of bibliography and the historical limitations imposed on women, the efforts undertaken by Pizan in this book, although apparently lacking the theoretical-conceptual delimitation of what is understood as bibliography nowadays, result in a remarkable repertoire of references, that deserve to be observed through the lens of bibliography and Knowledge Organization and considered by the field as a bibliographic gesture.